Thermal Performance Enhancement of Lithium-Ion Batteries Using Phase Change Material and Fin Geometry Modification - Sarmad Ali; Muhammad Mahabat Khan; Muhammad Irfan (World Electric Vehicle Journal, 2024)
The rapid increase in emissions and the depletion of fossil fuels have led to a rapid rise in the electric vehicle (EV) industry. Electric vehicles predominantly rely on lithium-ion batteries (LIBs) to power their electric motors. However, the charging and discharging processes of LIB packs generate heat, resulting in a significant decline in the battery performance of EVs. Consequently, there is a pressing need for effective battery thermal management systems (BTMSs) for lithium-ion batteries in EVs. In the current study, a novel experimental BTMS was developed for the thermal performance enhancement of an LIB pack comprising 2 × 2 cells. Three distinct fin configurations (circular, rectangular, and tapered) were integrated for the outer wall of the lithium-ion cells. Additionally, the cells were fully submerged in phase change material (PCM). The study considered 1C, 2C, and 3C cell discharge rates, affiliated with their corresponding volumetric heat generation rates. The combination of rectangular fins and PCM manifested superior performance, reducing the mean cell temperature by 29.71% and 28.36% compared to unfinned lithium-ion cells under ambient conditions at the 1C and 2C discharge rates. Furthermore, at the 3C discharge rate, lithium-ion cells equipped with rectangular fins demonstrated a delay of 40 min in reaching the maximum surface temperature of 40 <semantics>°</semantics>C compared to the unfinned ambient case. After 60 min of battery discharge at the 3C rate, the cell surface temperature of the rectangular fin case only reached 42.7 <semantics>°</semantics>C. Furthermore, numerical simulations showed that the Nusselt numbers for lithium-ion cells with rectangular fins improved by 9.72% compared to unfinned configurations at the 3C discharge rate.